Hubungan Tingkat Stres dengan Kualitas Tidur pada Lansia di Desa Urutsewu Wilayah Kerja Puskesmas Ampel Boyolali - Nala Siwi, Wahyu; Agung Pambudi, Hubertus; Febryanto, Dwi (Green Publisher Indonesia, 2025)
The elderly are an advanced stage of human life which is characterized by physiological decline. Various problems and events that arise in daily life can trigger stress. Stress in the elderly occurs due to pressure caused by stressors who demand adjustments from the elderly and unpreparedness to fight the changes experienced. Stress caused by life events such as the death of a loved one or financial difficulties can contribute to poor sleep quality. The quality and quantity of sleep are affected by several factors, including illness, fatigue, drug consumption, nutrition, environment, motivation and stress. This study aims to prove the relationship between stress levels and sleep quality in the elderly in Urutsewu Village, the working area of the Ampel Boyolali Health Center. This research is quantitative with a cross-sectional approach, using the elderly as a research sample. A sample of 59 elderly people used the total sampling technique. The measuring instrument uses the PSS10 questionnaire (Perseived stress scale) to measure stress levels and the PSQI (Pittsburgh Sleep Quality Index) questionnaire to measure sleep quality analyzed using the Chi Square test. A total of 30 elderly people (50.8%) experienced severe stress, there were 29 elderly people (49.2%) experienced mild stress. A total of 40 elderly people (67.8%) experienced poor sleep quality, there were 19 elderly people (32.2%) experienced good sleep quality. Fisher's test results were obtained with a significant p value = 0.000 (p<0.05). Based on the results of the study, it was shown that there was a relationship between stress levels and sleep quality in the elderly in Urutsewu Village, the working area of the Ampel Boyolali Health Center.